Pengaruh Pengelompokan Berdasarkan Gaya Belajar Dengan Pendekatan Problem Solving Terhadap Hasil Belajar Dan Aktivitas Siswa Kelas Xi Sma Negeri 1 Dolo - Ferdiansyah Ferdiansyah; Baharuddin Hamzah; Irwan Said (Mitra Sains, 2017)
Internal factors greatly affect the success of students’ learning. Identify the learning style can be used for grouping students in learning so that students can learn in a proper way, comfortable and positive. This study aims to: (1) Describe the differences in learning outcomes and students’ activity with problem solving approach between grouping based on learning styles and grouping not based on learning styles, (2) Describe the interaction effect of grouping based on learning styles in a problem solving approach with learning style of each students towards their learning outcomes and activity. Population of this study were the students of the grade XI IPA in SMAN 1 Dolo, and with purposive sampling technique, the samples taken were the students of the grade XI IPA 1 and XI IPA 2. Collecting data using a VAK (visual-auditory-kinesthetic) learning styles questionnaire, objective tests, and students’ activity observation sheet. This type of research is quasy experiment. Data were analyzed using two-way ANOVA test. Based on the results of data analysis can be concluded that: (1) There are differences in learning outcomes and students’ activity with problem solving approach between grouping based on learning styles and grouping not based on learning styles, (2) There are interactions of grouping based on learning styles in a problem solving approach with learning style of each students towards their learning outcomes, but there is no interaction of grouping based on learning styles in a problem solving approach with learning style of each students towards their activity.